ENERGY CULTURES AND SUSTAINABILITY IN BIOFUEL PRODUCTION - Mascarenhas Santos, Maria do Socorro; Silva, Cesar José da; Cruz, Sandra Helena da; Batistote, Margareth; Cardoso, Claudia Andrea Lima (REVISTA DE AGRICULTURA NEOTROPICAL, 2022)
Energy cultures are emerging as viable renewable energy sources because they satisfy sustainability requirements. The present study involves a survey regarding the technological characteristics for sugarcane and sweet sorghum energy crops, in addition to their potential for bioethanol production. An exploratory survey was conducted regarding the agronomic and technological characteristics of cane and sorghum. Pre-inmates were produced with YPSAC 5% liquid medium, sterilized and 0.10 grams of yeasts FT858 and Pedra-2 were inoculated and incubated at 30 °C for 10 h at 250 rpm. After the production, the cells were recovered by centrifugation, at 105 rpm, resulting in a 10 mg mg-1 concentration of moist dough. This dough was subsequently inoculated in the fermentative medium consisting of a base of sorghum broth and cane without pH correction with a 22 °Brix. Ethanol was analysed by gas chromatography and amino acids by high-efficiency liquid chromatography. Sorghum broth presented a greater availability of serine, arginine, alanine, threonine, and tryptophan amino acids. Yeast hers presented fermentative efficiency for both substrates, but the largest ethanol production occurred in sorghum broth. The results demonstrated that sugar sorghum may be used for energy purposes.